INSKRIPSI ARAB PADA MATA UANG KESULTANAN SAMUDERA-PASAI DAN KESULTANAN MALAKA ABAD KE-13 HINGGA AWAL ABAD KE-16 - Gumilar, Agung; Nurhayati, Fitri; Hidayat, Hendi; Musni, M. Jailani; Supardi, Adi (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2022)
According to a large number of chronicles and records, Islam is thought to have entered Nusantara directly from the Arabian Peninsula as early as the VII century AD. However, the power of Islam as a political entity has not appeared in the region since the end of the XII and XIII centuries AD. The period was marked by the introduction of a number of Arabic-inscribed currencies minted by local Muslim rulers in an effort to propagate the Islamic religion. The method used in this study is a qualitative descriptive method based on the humanities. The purpose of this research is to find out the type of khat (writing style) as well as the context of the terms contained in the currency of the Samudera-Pasai and Melaka sultanates in an effort to uncover the history of the greatness of Samudera-Pasai and Malacca, which are located on the Spice Route.